Islam and Professional Identity; Exploring the Influence of Religion in Shaping the English Teacher Professional Identities in Indonesia and Thailand - Zulfi Zumala Dwi Andriani; Naza Ilil Mubarokah; Siti Hawa Luemea (Universitas Muhammadiyah Malang, 2026)
This study explores the influence of Islamic values on the professional identity of muslim english teachers in indonesia and thailand. while existing literature on teacher identity often emphasizes gender, race, and christian contexts, the role of islam remains underexamined. employing a narrative inquiry approach, this research draws on in-depth interviews and classroom observations of two english teachers—one from a pesantren in Indonesia and another from an islamic private school in southern Thailand. Thematic analysis reveals three key dimensions through which islam shapes teacher identity: as a motivational force in choosing the profession, as integrated content within english teaching materials, and as a guiding framework for upholding students’ religious values. The findings suggest that religious identity significantly informs pedagogical practices and teacher-student interactions. However, the prioritization of moral and religious instruction may at times overshadow the development of students’ English language proficiency. The study recommends that school stakeholders critically evaluate curriculum design to ensure a balanced integration of religious values and language competency.